Multilingualism in Indonesian Literature: A Literary Review from the Perspective of Anthropolinguistics - Mu'in, Fatchul; Noortyani, Rusma; Sibarani, Robert (Tradition and Modernity of Humanity, 2021)
There is an interesting problem to raise, namely the use of unique language symptoms in Indonesian literary works. The uniqueness of language use in Indonesian literary works can be seen from two or more languages in Indonesian literary works. The use of two or more languages is called multilingualism in Indonesian literature. Multilingualism in Indonesian literary works is seen as "the overlapping use of language in Indonesian literature." Using more than one language can interfere with reading fluency for readers who do not come from the same culture. However, if we face literary works with multilingualism phenomena, we must respond and understand them. Duranti (1997: 21) explains that Anthropolinguistics emphasizes language as an expression of people's mindset. Anthropolinguistics views language as a set of cultural applications.